Wild-Type Measles Viruses with Non-Standard Genome Lengths - Bankamp, Bettina; Liu, Chunyu; Rivailler, Pierre; Bera, Jayati; Shrivastava, Susmita; Kirkness, Ewen F.; Bellini, William J.; Rota, Paul A. (PLOS ONE, 2014)
The length of the single stranded, negative sense RNA genome of measles virus (MeV) is highly conserved at 15,894 nucleotides (nt). MeVs can be grouped into 24 genotypes based on the highly variable 450 nucleotides coding for the carboxyl-terminus of the nucleocapsid protein (N-450). Here, we report the genomic sequences of 2 wild-type viral isolates of genotype D4 with genome lengths of 15,900 nt. Both genomes had a 7 nt insertion in the 3′ untranslated region (UTR) of the matrix (M) gene and a 1 nt deletion in the 5′ UTR of the fusion (F) gene. The net gain of 6 nt complies with the rule-of-six required for replication competency of the genomes of morbilliviruses. The insertions and deletion (indels) were confirmed in a patient sample that was the source of one of the viral isolates. The positions of the indels were identical in both viral isolates, even though epidemiological data and the 3 nt differences in N-450 between the two genomes suggested that the viruses represented separate chains of transmission. Identical indels were found in the M-F intergenic regions of 14 additional genotype D4 viral isolates that were imported into the US during 2007–2010. Viral isolates with and without indels produced plaques of similar size and replicated efficiently in A549/hSLAM and Vero/hSLAM cells. This is the first report of wild-type MeVs with genome lengths other than 15,894 nt and demonstrates that the length of the M-F UTR of wild-type MeVs is flexible.